Music Composition Alun Segara | Komposisi Musik Alun Segara - I Pande GedeYudista Wijasa; Ni Putu Hartini (Pusat Penerbitan LPPMPP ISI Denpasar, 2022)
This work is entitled Segara Square. Alun Segara is a utterance of someone's words inspired by the stylist himself to make a piece of musical art in the form of a composition, as a requirement for the final assignment of an undergraduate course at the Indonesian Art Institute, Denpasar. Alun Segara was inspired when the stylist went to the beach. Alun Segara in the true sense is a big wave. In discussing this word, it is a word of speech from the village community on the island of Nusa Penida, especially the people of Nusa Penida when the community will sail to the sea to find bad weather, that word is the typical language used by the community when the weather is bad at sea. From this incident, the stylist wanted to make it into a composition. In this work, the stylist makes a creative percussion by showing the composition of the shape of the waves and transforming it into a new musical composition using the Gong Kebyar barungan. The stylist describes this phenomenon in the form of a new creative percussion entitled Alun Segara. A new piece of music that the stylist picked up directly, the stylist saw it directly on the beach of Nusa Penida, which inspired a musical composition so that a creative percussion composition was realized. This work, of course, does not leave elements of Balinese gamelan playing in general. This work processes musical elements such as: tempo, rhythm, dynamics, melody, and harmony. It is from this element of music that the stylist creates rhythmic and melodic works.